2017
DOI: 10.13189/eer.2017.050405
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Objects: Mangrove Area Extraction Using Remote Sensing and Aerial LiDAR Data in Roxas, Oriental Mindoro

Abstract: The Phil-LiDAR 2 program aims to extract the natural resources of the Philippines from the available two points per square meter LiDAR data. Mangroves, being coastal resources, were one of the foci of this program under the Aquatic Resources Extraction from LiDAR Surveys (CoastMap). The object-based image analysis (OBIA) approach, and support vector machine (SVM) algorithm were utilized to classify three major classes from the LiDAR data, namely: mangrove, other vegetation, and non-vegetation. Object feature v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Long et al [44] have achieved an overall accuracy of 93% in using Landsat images for mangrove forests using decision tree classification only. Researchers in mangrove RS tend to use SVM [80,88], MLC [75], RF [81], and ANN [53], among others. Since these classifiers are non-parametric, they do not need the requirements for normality.…”
Section: Different Approaches In Discriminating Mangroves From Other ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Long et al [44] have achieved an overall accuracy of 93% in using Landsat images for mangrove forests using decision tree classification only. Researchers in mangrove RS tend to use SVM [80,88], MLC [75], RF [81], and ANN [53], among others. Since these classifiers are non-parametric, they do not need the requirements for normality.…”
Section: Different Approaches In Discriminating Mangroves From Other ...mentioning
confidence: 99%
“…The study clarified that SVM has shown to be more effective (99%) in discriminating mangroves from other land cover. This algorithm is particularly promising when used in mangrove classification using high-resolution datasets such as LiDAR derivatives [79,86,87] compared to the results of Songcuan et al [88] and Gevaña et al [77] (92-95%) using low-resolution datasets. This study supports the findings of Pham et al [30], which showed that among the machine learning algorithms, SVM produced higher overall accuracy in both cases.…”
Section: Different Approaches In Discriminating Mangroves From Other ...mentioning
confidence: 99%
“…Recent studies that document the spatial extent of mangrove forest in the country integrates very highresolution aerial data to provide ne-resolution mangrove distribution maps (Luna et al, 2017;Cabili et al, 2018). While it yields higher accuracy and better image resolution results compared to previous satellite-derived mangrove forest maps, it is often limited to smaller spatial scales due to the limited availability of high-resolution images.…”
Section: Introductionmentioning
confidence: 99%
“…These restorative activities need to be implemented according to a high-resolution map for the entire landscape of the PHU [16]. As the map will cover an extensive area, the restoration of the whole PHU area be costly as well as require high levels of energy, and time [22]. Therefore, it may be necessary to divide the tropical PHU into individual sub-PHUs (sub-domes or mini-domes), independently identifying a smaller space but still part of the whole hydrological system [15].…”
Section: Introductionmentioning
confidence: 99%